2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00194
|View full text |Cite
|
Sign up to set email alerts
|

Learning Semantic Segmentation From Synthetic Data: A Geometrically Guided Input-Output Adaptation Approach

Abstract: Recently, increasing attention has been drawn to training semantic segmentation models using synthetic data and computer-generated annotation. However, domain gap remains a major barrier and prevents models learned from synthetic data from generalizing well to real-world applications. In this work, we take the advantage of additional geometric information from synthetic data, a powerful yet largely neglected cue, to bridge the domain gap. Such geometric information can be generated easily from synthetic data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
124
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(125 citation statements)
references
References 54 publications
0
124
0
1
Order By: Relevance
“…Joint consideration of pixel-and feature-space domain adaptation is studied in [13]. For segmentation task, it is also found that aligning the segmentation space is a more effective DA strategy [44,7]. Besides the adversarial training-based DA methods [13,44,20], other lines of work on semantic segmentation borrow the idea from selftraining [33] or co-training [47].…”
Section: Domain Adaptive Semantic Segmentationmentioning
confidence: 99%
“…Joint consideration of pixel-and feature-space domain adaptation is studied in [13]. For segmentation task, it is also found that aligning the segmentation space is a more effective DA strategy [44,7]. Besides the adversarial training-based DA methods [13,44,20], other lines of work on semantic segmentation borrow the idea from selftraining [33] or co-training [47].…”
Section: Domain Adaptive Semantic Segmentationmentioning
confidence: 99%
“…Several methods train networks based on ground-truth labels and have been successfully applied to many tasks, such as monocular depth prediction [9,10,27,28], optical flow [8,19,35,38] and camera pose estimation [22,23,24]. To leverage the multiple cues, the tasks can be tackled jointly by fusing boundary detection [20], the estimation of surface normals [28], semantic segmentation [4,46,50], etc.…”
Section: Related Workmentioning
confidence: 99%
“…A curriculum-style learning approach is proposed in [16], where firstly the easier task of estimating global label distributions is learned and then the segmentation network is trained forcing that the target label distribution is aligned to the previously computed properties. Many other works addressed the domain adaptation problem with various techniques, including GANs [29], [45], cycle consistency [11], [46], output space alignment [47], [48], distillation loss [17], [49], class-balanced selftraining [50], conservative loss [51], geometrical guidance [52], adaptation networks [53] and entropy minimization [54].…”
Section: Related Workmentioning
confidence: 99%